Cyberlaw text and cases - Ferrera, Gerald R. (South-Western / Cengage Learning, 2012)
The third edition of CYBERLAW: TEXT & CASES guides readers through the complete business lifecycle--from idea to operation to dissolution--while examining the legal, managerial, and ethical issues affecting technology at each stage. Excerpted cases thoroughly explain the law in every chapter, while a running case about Google helps readers understand the real-world legal implications of operating a technology company today.